Thrombomodulin expression by human keratinocytes. Induction of cofactor activity during epidermal differentiation. - Raife, T J (1994)
Thrombomodulin is an endothelial cell surface glycoprotein that inhibits the procoagulant activities of thrombin and accelerates activation of the anticoagulant protein C. Because protein C deficiency is associated with cutaneous thrombosis, we investigated the expression of thrombomodulin in human skin. Thrombomodulin was detected by immunohistochemical staining both in dermal endothelial cells and in epidermal keratinocytes. Within the epidermis, thrombomodulin staining was limited to keratinocytes of the spinous layer, suggesting that thrombomodulin is induced when basal keratinocytes begin to terminally differentiate. Thrombomodulin expression also correlated with squamous differentiation in epidermal malignancies; little or no thrombomodulin staining was seen in five basal cell carcinomas, whereas strong thrombomodulin staining was observed in each of five squamous cell carcinomas. Human foreskin keratinocytes cultured in medium containing 0.07 mM calcium chloride synthesized functional thrombomodulin with cofactor activity comparable to thrombomodulin in human umbilical vein endothelial cells. Stimulation of keratinocyte differentiation with 1.4 mM calcium chloride for 48 h produced 3.5-, 3.2-, and 5.6-fold increases in thrombomodulin cofactor activity, antigen, and mRNA, respectively. These observations suggest that thrombin is regulated by keratinocyte thrombomodulin at sites of cutaneous injury, and indicate a potential role for thrombomodulin in epidermal differentiation.